The 2009 survey of consumer payment choice - Kevin Foster; Erik Meijer; Scott Schuh; Michael A. Zabek (Federal Reserve Bank of Boston, 2011)
This paper presents results of the 2009 Survey of Consumer Payment Choice (SCPC), along with revised 2008 SCPC data. In 2009, the average U.S. consumer held 5.0 of the nine payment instruments available, including cash, and used 3.8 of them during a typical month. Between the 2008 and 2009 surveys, a period that includes the trough of the latest recession, consumers significantly increased their use of cash and close substitutes for cash, such as money orders and prepaid cards. At the same time, consumers reduced their use of credit cards and (to a lesser extent) debit cards, as well as payments made using a bank account number. Weaker economic conditions, new government regulations, and bank pricing of payment card services all likely contributed to the shift back toward cash. However, it is difficult to determine how much each of these factors contributed, and whether the shift is transitory or permanent, without more data and research on consumer payment choice. In 2009, one in three consumers had a prepaid card and nearly as many had a nonbank payment account online, while 3 percent made a mobile payment. By focusing on payments by consumers only, the SCPC complements the recent 2010 Federal Reserve Payment Study, which describes the entire noncash payments economy.
Keywords: D12; D14; E42; 330; Zahlungsverkehr; Konsumentenverhalten; Finanzmarktkrise; USA